TEMPERATURE CONTROLLER - SEKINE SADAO; SEKIYA MASAHIRO (1995)
PURPOSE:To accurately control the heating temp. of an object to be heated to a set upper limit value or below by detecting a Curie tap. and calculating the end point of heating at the time of induction heating. CONSTITUTION:The high-frequency current value flowing in an induction heating coil 3 is detected by an output ammeter 5 at the time of subjecting a steel bar 4 to high-frequency induction heating. The change in the detected high-frequency current is calculated by an arithmetic control section 6 and the oscillation operation of an oscillator 1 is shut off or controlled, by which the upper limit temp. for heating of the steel bar 4 is controlled. At this time, the impedance of the coil 3 is changed by magnetic conversion of the steel bar 4 heated up to the Curie temp. to paramagnetism if the circuit constant of an impedance matching circuit 2 is previously so set as to maximize the current flowing in the coil 3. The impedance matching conditions are then broken and the current flowing in the coil 3 changes. As a result, excessive overheating is prevented without using a sensor, etc.